2015
DOI: 10.1186/s12864-015-1736-5
|View full text |Cite
|
Sign up to set email alerts
|

The sulfur/sulfonates transport systems in Xanthomonas citri pv. citri

Abstract: BackgroundThe Xanthomonas citri pv. citri (X. citri) is a phytopathogenic bacterium that infects different species of citrus plants where it causes canker disease. The adaptation to different habitats is related to the ability of the cells to metabolize and to assimilate diverse compounds, including sulfur, an essential element for all organisms. In Escherichia coli, the necessary sulfur can be obtained by a set of proteins whose genes belong to the cys regulon. Although the cys regulon proteins and their impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 40 publications
(66 reference statements)
1
16
0
1
Order By: Relevance
“…The comparison of NrtT with putative orthologues using the BLASTP tool confirmed similarities with nitratebinding proteins from different species of the genus Xanthomonas and the two alkanesulfonate-binding proteins from X. citri, SsuA1 and SsuA2 [17]. Moreover, the same genome organization found in X. citri is present in Xanthomonas campestris, another important phytopathogen that infects citrus plants but with a different mechanism (Fig.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The comparison of NrtT with putative orthologues using the BLASTP tool confirmed similarities with nitratebinding proteins from different species of the genus Xanthomonas and the two alkanesulfonate-binding proteins from X. citri, SsuA1 and SsuA2 [17]. Moreover, the same genome organization found in X. citri is present in Xanthomonas campestris, another important phytopathogen that infects citrus plants but with a different mechanism (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Furthermore, from the list of importers, 14 genes are related to the uptake of nitrate/taurine or sulfate/aliphatic sulfonates and akanesulfonates, showing that these compounds might confer on the bacterium some advantage during its growth and evidencing the relevance of sulfur in this process. In fact, during growth of the bacterium in LB broth and XAM1 media, the ABC transporters responsible for sulfate uptake (SbpCysUWA) and the additional systems related to the transport of alkanesulfonates and/or organosulfur compounds (SsuABC1 and SsuABC2) are differentially induced [17], suggesting a regulation based on sulfur availability. Studies have shown a significant and continuous activation of the sbpcysUWA promoter during the first stages of infection of X. citri in C. sinensis leaves, indicating the need for sulfate in these conditions [18].…”
mentioning
confidence: 99%
“…At a minimum, sulfur is required for growth of all known bacteria under all known conditions because it is a main component of an amino acid (methionine) present in all translated proteins (1) . Sulfate is one of the most widely available and utilized sulfur sources for terrestrial bacteria, which is highlighted by conservation of the sulfate transport pathway genes cysAUWP across many proteobacterial strains including xanthomonads (10) . That certain clades of Luteibacter have altered abilities to metabolize sulfate compared to closely related outgroups like Xanthomonas , speaks to a difference in ecological niche for these strains compared to their more widely studied relatives.…”
Section: Sulfur Acquisition By Luteibacter Under Natural Growth Condimentioning
confidence: 99%
“…It is worth noting that cysA, cysB and serineO were upregulated in the presence of Ni 2+ and Fe 3+ . Sulfate/thiosulfate import ATP-binding protein (cysA) and transport sulfate as a sulfur source for cysteine biosynthesis [34]. Moreover, serine O-acetyltransferase (serine O) catalyze the reaction: L-serine + acetyl-coenzyme A ⇆ O-acetyl-L-serine + coenzyme A [35], subsequently, the O-acetyl-L-serine can be converted into organic sulfur molecules cysteine [36].…”
Section: Discussionmentioning
confidence: 99%